Development of a professional competency framework for UK food science graduates. Issue 1 (23rd December 2019) - Weston, Emma; Foster, Tim; Crilly, Jim; Mossop, Liz
Abstract: Food science‐based graduates are a significant proportion of the United Kingdom (UK) food and drink industry's workforce. Aside from technical standards, there is no cohesive competency framework to support key stakeholders; employers, students, and degree providers. Clarity of desirable competencies for the range of graduate opportunities available would enable students to undertake effective career planning and personal development, and educators to refine programs to satisfy market needs. Using a previously developed language tool, a Likert style, industry‐wide online survey in UK and Republic of Ireland (ROI) was conducted involving 218 participants from a broad range of food science‐related employment areas, evaluated by a combination of descriptive and multivariate data analysis. The survey outcomes indicate types of desirable competencies in a food science graduate. The tailored competency framework, Competencies for Food Graduate Careers (CFGC), is a set of 48 elements across eight themes, outlining which are desirable for each of 14 typical initial graduate roles. To enhance the quality of "oven‐ready" graduates entering the food industry, it is recommended CFGC be used for careers education and competency development in higher education. The framework is aimed to have further applications for job specification development and also to improve awareness of careers in the food industry.